SOSIALISASI MEMBANGUN MEDIA DAKWAH DIGITAL: PENGEMBANGAN WEBSITE DAN APLIKASI UNTUK PAGUYUBAN ISTRI PENGURUS - Wati, Patnah; Riyadi, Slamet; Ratnawati, Dewi; Fauzan; Sobirin (CV SWA Anugerah, 2024)
This Community Service activity (PKM) aims to increase the accessibility and effectiveness of da'wah through digital media for the Executive Wives Association. In the digital era, the use of information technology is very relevant to spread Islamic values widely. This activity includes the development of a website and da'wah application, which includes training on how to manage da'wah content effectively. The methods used include presentations, discussions, and hands-on practice. The results of the activity showed an increase in participants' knowledge of digital da'wah media and the effectiveness of da'wah communication within the association. This activity is expected to contribute to the sustainability of da'wah in modern society. Key Words: community service, digital da'wah, da'wah media, information technology, community empowerment .